The Influence of Slovenian Traffic Safety Agency on Motor Vehicle Legislation - SVETINA, TOMAZ (Journal of Applied Engineering Science, 2012)
The objective of this paper is to provide an analysis of the type-approval system in the Republic of Slovenia. In this analysis Slovenian legislation regarding motor vehicles is compared to European Union legislation. Besides this the Slovenian Traffic Safety Agency’s influence on the above mentioned legislation is presented, as well as the legislation’s influence on safety and environmental friendliness.
Keywords: Periodical Technical Inspection; The Slovenian Traffic Safety Agency; Motor Vehicle Act; Type Approval